CONSUMER PROTECTION OF THE PRICE GAME IN ONE OF THE LARGEST MINIMARKETS IN INDONESIA - Abdul Hakim Amir; Gianto Al-Imron (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Indomaret is one of the best-selling minimarket in Indonesia, however, price games often occur and do not realized by the consumers. This study aims to provide information about legal protection for consumers who feel disadvantaged by the indomaret minimarket who play price games and find out the legal consequences. The study method used normative law, which was the assessment approach to the principles and systematic system of law in the regulation of existing laws through a statute approach and a conceptual approach. The results of this study are violations committed by business owners against the consumers including 3 existing regulations in the case of differences in entry prices in the BW regulations (Burgerlijk Wetboek), consumer protection laws, Regulation of the Minister of Trade No. 35 of 2013. First, regarding acts against the lawin the BW, regarding consumer rights with consumer obligations in consumer protection laws, and Regulation of the Minister of Trade No. 35 of 2013 concerning the inclusion of prices of goods. Minimarkets that play price games, such as differentiating prices on display with cash, include criminal acts that are detrimental to consumers thus there is legal protection in force.